Mimetic Faces: On Luiz Costa Lima's The Control of Imaginary - Alberto Moreiras (Studies in 20th & 21st Century Literature, 1993)
Mimetic Faces: On Luiz Costa Lima's The Control of Imaginary
Keywords: The Control of the Imaginary; Jochen Schulte-Sasse; mimesis; Luiz Costa Lima; imagination; modernity; art; expression; reason; Mimesis e modernidade; intellectualism; community; social identity; self; Aristotle; Freud